Effect of Mirror Image Therapy Combined with Whole Body Vibration Training on Unilateral Spatial Neglect after Stroke - YANG Keqin; ZHANG Li; ZHANG Chunyan; CHEN Chengcheng; QI Hui; ZHAO Bin (康复学报)
ObjectiveTo explore the effect of mirror image therapy combined with whole body vibration training on the rehabilitation of patients with unilateral spatial neglect after stroke.MethodsAccording to the inclusion criteria, patients with unilateral spatial neglect after stroke who attended the rehabilitation center of the Second Affiliated Hospital of Heilongjiang University of Traditional Chinese Medicine from October 2019 to December 2020 were selected. After the hospital ethics committee approvaled, 90 eligible patients were included. According to the random grouping method, participants were divided into mirror image therapy group, whole body vibration training group and combination group, with 30 cases in each group. There was no statistically significant difference in the general data of the three groups. The mirror image therapy group used a mirror box dedicated to mirror therapy for upper limb and hand mirror training. According to the differences in the patient's functional status, different movement tasks were selected, such as grooming, eating, buttoning, turning books, and holding objects. The whole body vibration training group adopted whole body vibration training, using the Wellengang vibration therapy instrument developed by SVG company in Germany, the vibration frequency with 30 Hz, the vibration amplitude with 3 mm, the total treatment time was 30 minutes, 1 time/d, 6 days a week for 8 weeks. The combined group used both mirror image therapy (20 min) + whole body vibration training (10 min) for 6 days once a week for 8 weeks. All three groups were treated with the Catherine Bogor scale (CBS) before treatment and at the time of treatment for 8 weeks, respectively, to assess the severity of the spatial neglect of the patients. The mini-mental status examination (MMSE) was used to evaluate the cognitive dysfunction of patients. The simplified Fugl-Meyer Assessment scale (FMA) was used to evaluate the patient's upper limb motor function. The Barthel index (BI) was used to measure the self-care ability of patients.ResultsBefore treatment, there was no significant difference in CBS, MMSE, FMA and BI scores among the three groups (P>0.05). After 8 weeks of treatment, the CBS scores of the three groups were significantly lower than those before treatment, however MMSE, FMA and BI scores were significantly higher than those before the treatment, but the combined group was better than the mirror image group and the whole body vibration training group, and the difference was statistically significant respectively (P<0.05).ConclusionMirror image therapy combined with whole body vibration training can effectively improve the degree of spatial neglect and cognitive dysfunction in patients with unilateral spatial neglect after stroke, and enhance upper limb motor function and self-care ability.